PERENCANAAN SUMBER DAYA MANUSIA DALAM PENINGKATAN MUTU MAN 1 TULUNGAGUNG DI ERA REVOLUSI INDUSTRI 4.0 - Tiniyyah, Antiq Kusthon; Maunah, Binti (Universitas Islam Negeri Alauddin Makassar, 2023)
The logical impact of efforts to improve the quality of education is the need to improve the quality of components in the education system, including human resources. The aim of this research is to determine human resource planning in improving the quality of education at MAN 1 Tulungagung City. This research uses a qualitative approach using descriptive qualitative methods. Data collection was carried out through observation, interviews and documentation techniques. The results of this research are that Human Resources Planning at MAN 1 Tulungagung is carried out in planning the educators and educational personnel needed in the madrasah, recruitment, as well as the appropriate placement of educators and educational personnel. Educators and education staff are given guidance in the form of seminars as well as education and training to improve their abilities and continue to work effectively. The quality of education at MAN 1 Tulungagung is classified as very good, MAN 1 Tulungagung is accredited A. Human resource planning at MAN 1 Tulungagung in improving the quality of education is considered successful, planning is implemented well and the quality of education is very good. MAN 1 Tulungagung students experienced an improvement in terms of achievement, this year a higher percentage of students were accepted into higher education than the previous year. It is hoped that the implications of the findings of this research can be a reference for Madrasas to carry out human resource planning well and continuously in order to realize superior Madrasah quality and be able to compete in the era of the Industrial Revolution 4.0.